The Erasmus+ Programme and Its Impact on Labour Market in the Czech Republic - Smetanová, Ema; Antal, Jarolím, 1986-; Mammadov, Orkhan; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2024)
This thesis examines the impact of the Erasmus Programme on the labor market in the Czech Republic, focusing on the employability and career trajectories of its participants. Through a comprehensive analysis that includes a literature review, detailed evaluation of the Erasmus Programme, and qualitative interviews with key stakeholders, the study reveals that Erasmus graduates acquire valuable skills such as language proficiency, intercultural communication, adaptability, and problem-solving abilities, which are highly valued by employers. While the direct impact on unemployment rates is limited, the programme significantly enhances participants' professional success and contributes to a more skilled, adaptable, and globally competent workforce. The findings underscore the importance of continued support and expansion of the Erasmus Programme for advancing educational and professional excellence within the European Union.
Vedoucí práce: Jarolím Antal
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor bakal. práce]; bakalářské práce; bachelor's theses